Dual Axis Solar Tracking System in Perlis, Malaysia - Zulkafli, R.S.; Bawazir, A.S.; Amin, N.A.M.; Hashim, M.S.M.; Majid, M.S.A.; Nasir, N.F.M. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Sunlight is an abundant source of energy and this energy can be harnessed successfully using solar photovoltaic panels and convert it into electrical energy. However, the conversion efficiency of a normal PV panel is low. One of the main reasons is the power output of a PV panel is dependent directly on the light intensity. As the position of the sun is changing continuously from time to time, the absorption efficiency of an immobile solar panel would be significantly less at a certain time of the day and year. Therefore, to maximize the energy generation and improve the efficiency, a solar tracker comes into play. This paper presents the design and construction of an inexpensive active dual axis solar tracking system for tracking the movement of the sun to get the maximum power from the solar panels. It uses Light Dependent Resistors (LDR) to sense the position of the sun which is communicated to an Arduino Uno microcontroller. An algorithm is implemented to control DC geared motor’s movements which maintaining the solar PV panel position so that it will perpendicularly facing towards the sun at all the effective time. Performance for both fixed and dual-axis solar tracker was compared. Evaluation results show that the dual-axis solar tracking system performs 44.7% better than the fixed solar tracking system.